Answer:
108
Step-by-step explanation:
Answer:
y = 6x - 43
Step-by-step explanation:
(6, -7) and (8,5)
m=(y2-y1)/(x2-x1)
m=(5 + 7)/(8 - 6)
m= 12/2
m = 6
y - y1 = m(x - x1)
y + 7 = 6(x - 6)
y + 7 = 6x - 36
y = 6x - 43
Answer:
yes; 4² + 3² = 5²
Step-by-step explanation:
Pythagorean theorem.
In a right triangle the square of the hypotenuse is equal to the sum of the squares of the other two sides. Hypotenuse is the longest side of the triangle.
4² + 3² = 5²
16 + 9 = 25
25 = 25
Answer:
y = 50
Step-by-step explanation:
Firstly, let's make an equation. We know that when y is 15, x is 3. Or, in other words, y is 5 times what x is. Therefore we can use the equation, y = 5x.
Now, just plug x into the equation.
y = 5(10)
y = 50
Csc a - sin a = cos a cot a
1/sin a - sin a = cos a (cos a / sin a)
(1 - sin^2 a)/sin a = cos^2 a/sin a
cos^2 a/sin a = cos^2 a/sin a
Therefore, the given equation is an identity.